Cephalometrıc Evaluatıon In "Obstructıve Sleep Apnea" Syndrome - O. Bengi; H. Ölmez; D. Sağdıç; Ü. Gürton; M. Gerek (Galenos Yayinevi, 1997)
In this study, linear, angular, and area measurements of lateral cephalometric radiograms of 20 adult OSA cases were compared with those of 60 adults who do not have any subjective signs and symtoms of OSA. The control group was divided into skeletal Cl,1, Cl.2 and Cl.3 subgroups to determine the differences and similarities of OSA cases with controls who have different skeletal patterns. Comparisons were made by means of non-parametric Man Whitney-U test. Increases in craniocervical angulation and soft palate length and decreases in nasopharengeal area were found to be the common differences between OSA and skeletal Cl.1, Cl.2, and Cl. 3 cases.